Experimental study on the performance of an si engine fueled by waste plastic pyrolysis oilgasoline blends - Khairil; Riayatsyah T.M.I.; Bahri S.; Sofyan S.E.; Jalaluddin J.; Kusumo F.; Silitonga A.S.; Padli Y.; Jihad M.; Shamsuddin A.H. (MDPI AG, 2023)
ASTM standards; Brakes; Chemical reactors; Engines; Ethylene; Physicochemical properties; Plastic recycling; Polyethylene terephthalates; Polymer blends; Pyrolysis; Testing; Automotive technology; Brake specific fuel consumption; Engine performance; Fixed bed reactor; Noise vibration harshness; Performance indicators; Research octane number; Standard test method; Gasoline